Transient analysis of trailing edge noise assisted by wavelet-based beamforming and flow visualisation. (26th May 2022) - Yu, Jiaming; Chen, Wangqiao; Zhou, Teng; Lee, Cunbiao; Huang, Xun
Abstract: This work focuses on the trailing edge flow-induced noise by studying the associated transient noise generation physics. A wavelet-based beamforming method is first performed to analyse the dynamics and correlations of the trailing edge noise problems in the time–frequency domain. The wavelet-based beamforming method is an extension of the conventional beamforming method in which the Fourier transform is substituted by the wavelet transform to perform the transient acoustic imaging. The transient process is interpretable by using this method, which is impossible for the previous conventional acoustic imaging techniques. To verify and showcase the proposed method, the velocity field obtained by particle image velocimetry is provided along with the time–frequency analysis of acoustic measurements. Next, a particular problem of trailing edge noise from an aerofoil is experimentally studied at the Reynolds number of O ( 1 0 5 ), where the intermittent nature of the underlying aerodynamic flow structures can be inferred by the proposed wavelet-based beamforming. To provide the complementary flow-field results, a secondary experiment is performed in a different wind tunnel around the same Reynolds number. The finding of the correlation between the flow field and acoustic imaging results constitutes the key contribution of this work. Finally, the analysis of the velocity flow field and of noise source image is used to elucidate the associated flow physics. Overall, the proposed method can help to achieve deepened physical insights into various transient and moving systems in underwater and aerospace systems. Highlights: The PIV and the proposed wavelet-based beamforming method are employed. The flow fluctuations, transient flow dynamics and the correlations are studied. The dynamics and correlations of the trailing edge noise are analysed.